2011
DOI: 10.1002/dvdy.22601
|View full text |Cite
|
Sign up to set email alerts
|

Budding behaviors: Growth of the limb as a model of morphogenesis

Abstract: Questions regarding morphogenesis have played second fiddle to those pertaining to pattern formation among the limb development set for some time. A recent series of publications has reinvigorated the search for mechanisms by which the limb bud arises, elongates and acquires its peculiar shape. While there are stage-specific variations, the theme that resonates across these studies is that mesoderm and cartilage cells in the limb bud exhibit polarity that drives directional movement and oriented division. Nonc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 88 publications
0
35
0
Order By: Relevance
“…Studies on the limb have shown that non-directional growth alone is unable to explain the shape changes the limb bud experiences during development. Rather, polarized cell activities, such as cell movement in the mesenchyme, appear to comprise the emergent properties that generate shape (Boehm et al, 2010;Hopyan et al, 2011). Results from work in our laboratory indicate that polarized cellular behaviors associated with cell movement are associated with facial shape (Li et al, 2013).…”
Section: Mechanisms Of Morphogenesismentioning
confidence: 84%
“…Studies on the limb have shown that non-directional growth alone is unable to explain the shape changes the limb bud experiences during development. Rather, polarized cell activities, such as cell movement in the mesenchyme, appear to comprise the emergent properties that generate shape (Boehm et al, 2010;Hopyan et al, 2011). Results from work in our laboratory indicate that polarized cellular behaviors associated with cell movement are associated with facial shape (Li et al, 2013).…”
Section: Mechanisms Of Morphogenesismentioning
confidence: 84%
“…For example, in the growth plate, loss of oriented cell behaviors leads to loss of proliferative column structure and generates bones that are reduced in length and greater in width. 46,81 One simple model derived from these observations is that oriented cell behaviors provide a driving force for tissue elongation in the developing skeleton, 46,84 analogous to a model previously proposed for events in zebrafish gastrulation. 85 In the context of the limb, this model has only been empirically tested in the growth plate, a tissue in which precise measurements of elongation have been performed.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 88%
“…For instance, propagating mechanical waves have been shown to mediate cooperative force transmission among epithelial cells in wound-healing assays [84]. In many biological processes, cell motion takes place on curved surfaces, as in cell renewal and repair in the highly folded intestine [85] and the shaping of the early limb bud in developing embryos [86]. The effect of curvature on the dynamics of epithelial cells is beginning to be explored in vitro by examining collective cell migration on cylindrical capillaries of varying radii [21].…”
Section: Discussionmentioning
confidence: 99%